Effect of waves on the leading-edge undulated tidal turbines. (February 2019) - Shi, Weichao; Atlar, Mehmet; Norman, Rosemary; Day, Sandy; Aktas, Batuhan
Abstract: This paper presents an investigation on the efficiency performance of the leading-edge undulated tidal turbine blades under the effect of waves. This biomimetic blade application is inspired by humpback whale flippers which provide these mammals with an exceptional manoeuvring ability that is mainly accredited to the beneficial of their leading-edge tubercles. The paper first presents the design, optimisation and experimental validation of these turbine models. With the aim of further validating the efficiency performance in a different testing environment as well as exploring the combined effect of the tidal current and wave interaction, a test campaign in a towing tank facility was conducted. Both regular and irregular wave conditions were considered combining with varying towing speeds to simulate the tidal current effect. The test results revealed that the leading-edge undulated turbine has a stable hydrodynamic performance over a combined range of current speeds and waves indicating that the overall performance was not affected considerably by the combined effects as opposed to the performance solely due to steady tidal current. Highlights: Biomimetic concept of applying leading-edge tubercles on a tidal turbine blade has been performed. Leading-edge tubercles have significant impacts on the improvement of the hydrodynamic performance. First practice of testing bioinspired tidal turbine blade in a towing tank facility under the wave and current. Power generation performance under waves were evaluated and proved the effectiveness of leading-edge tubercles under wave conditions.